PENGELOLAAN KARYAWAN DIFABEL PADA HOTEL BERBINTANG DI KOTA BANDUNG - Mulyadi, Tirta (Journal of Accounting and Management Innovation, 2020)
The study entitled "Management of Disabled Employees in Starred Hotels in Bandung" describes the implementation of management of disabled employees with the Workplace Disability Inclusion Assessment Tool approach from the Business Leadership Network, United States (USBLN) which consists of Recruitment, Employment, Diversity Supplying, Technology Accessions and Marketing. The locus of research is Sany Rosa Hotel, Travelo, Amaris, Sakti Hotel, Aston Pasteur, Trans Luxury, Hilton, Enhaii Hotel and Regata Hotel. This research was conducted with a descriptive method with a qualitative approach. There are five types of informants in this study, namely; academia, industry, society, government and media. From the results of data collection on recruitment aspects, it can be seen that the aspects of industry, especially hotels, have not yet carried out the implementation of recruitment as a whole. The application of employment to employees with disabilities at the hotel is limited to acceptance in accordance with the needs and specifications of the hotel. The application of diversity supplying has not been done because there is no information or data that reveals the existence of companies with disabilities. The application of technology to employees with disabilities in hotels is limited to spatial aspects. The application of marketing aspects in hospitality in this case is limited to the inclusion of friendly and generally intended for guests. This was done to enlarge the image of the hotel.Keywords : Management, Disable, Employee, Stars Hotel, Bandung.